Professional development as a collaborative endeavour of networked learning in higher educational settings: Dissemination of knowledge among teacher training professionals - Håkansson Lindqvist, Marcia; Jaldemark, Jimmy; Mozelius, Peter (Proceedings of the International Conference on Networked Learning, 2018)
University teachers continue to strive to take up mobile and blended learning technologies in their teaching practices and universities continue to support this work through professional development courses for university teachers. At Mid Sweden University, two projects have recently been carried out with the objective to develop higher education practices supported by mobile and blended learning technologies in teaching in practice. Professional development for university teachers was expected take place using an iterative design comprising five features: participating in a competence development course, planning trials, conducting trials, evaluating teaching and participating in a pedagogical seminar. In this paper, the preliminary results of the final interviews with 12 teacher educators will be presented. The interviews were carried out to explore beliefs regarding changes in teaching practices, following the completion of teacher professional development project. The results showed that the teacher educators in this study experienced change in the use of mobile and blended learning in their teaching through dialogue, collaboration, dissemination and networked learning. Three themes were identified. The first theme was collaboration. Here, the teacher educators expressed beliefs which could be related to collaboration for learning to use mobile and blended learning technologies in their teaching, supporting conditions for networked learning. This involved working and planning new technologies in new courses together. In the second theme, sharing is caring, the teachers in the study expressed helping each other out and supporting each other in the work to learn and use new technologies in their teaching. Support through pep talks and taking on learning new technologies as a group was one example of gaining knowledge about new technologies. In the third and final theme, the teacher educators’ expressed beliefs regarding dissemination as a way to share knowledge and experiences. Beliefs expressed here included learning through seeing what others were working with and exchanging knowledge. The teacher educators’ in this study also expressed the need for continued learning through collaboration and dissemination, as networked learning in their community of practice. How universities continue to provide professional development to support teachers’ continued work together in communities of practice through networked learning will be of importance. These efforts in professional development will provide possibilities to push forward change in teachers’ use of mobile and blended learning in their teaching practices.